Role of human salivary enzymes in bitter taste perception. (30th August 2022) - Schwartz, Mathieu; Brignot, Hélène; Feron, Gilles; Hummel, Thomas; Zhu, Yunmeng; von Koskull, Dorothee; Heydel, Jean-Marie; Lirussi, Frédéric; Canon, Francis; Neiers, Fabrice
Highlights: Expression of glutathione transferases in a large panel of subjects. Salivary glutathione transferases (SGTs) can metabolize bitter molecules. Multiple binding sites for bitter molecules in SGTs. Lower expression of SGT alpha 1 in saliva of people suffering taste disorders. Abstract: The molecules that elicit taste sensation are perceived by interacting with the taste receptors located in the taste buds. Enzymes involved in the detoxification processes are found in saliva as well as in type II cells, where taste receptors, including bitter taste receptors, are located. These enzymes are known to interact with a large panel of molecules. To explore a possible link between these enzymes and bitter taste perception, we demonstrate that salivary glutathione transferases (GSTA1 and GSTP1) can metabolize bitter molecules. To support these abilities, we solve three X-ray structures of these enzymes in complexes with isothiocyanates. Salivary GSTA1 and GSTP1 are expressed in a large panel of subjects. Additionally, GSTA1 levels in the saliva of people suffering from taste disorders are significantly lower than those in the saliva of the control group.